2012
DOI: 10.2169/internalmedicine.51.7737
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Deafness and Facial Diplegia in Guillain-Barré Syndrome: Radiological Depiction of Facial and Acoustic Nerve Lesions

Abstract: We herein report a 26-year-old man with Guillain-Barré Syndrome (GBS) coexisting facial nerve palsy (FP) and deafness. He developed deafness, facial weakness, and limb weakness and numbness. Neurological examination showed facial diplegia, bilateral hypoacusia, areflexia and sensorimotor deficits in the distal limbs. The nerve conduction study findings supported the diagnosis of the demyelinating polyneuropathy. An audiogram revealed sensorineural hearing loss of 40-50 dB. Auditory brainstem responses disclose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…Our findings indicate that HHL can also arise from pathologies of cochlear Schwann cell (schwannopathy) or nodal structures (nodopathy), rather than synaptopathy. Indeed, some patients with demyelinating disorders such as CMT disease and GBS have auditory deficits, associated with reduced ABR amplitudes and increased latencies 60 61 62 63 64 . Our animal model shares mechanistic similarities with GBS, where Schwann cells are specifically and transiently damaged 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that HHL can also arise from pathologies of cochlear Schwann cell (schwannopathy) or nodal structures (nodopathy), rather than synaptopathy. Indeed, some patients with demyelinating disorders such as CMT disease and GBS have auditory deficits, associated with reduced ABR amplitudes and increased latencies 60 61 62 63 64 . Our animal model shares mechanistic similarities with GBS, where Schwann cells are specifically and transiently damaged 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Although it's a rare finding, there are few case reports describing this entity (Takazawa, et al . )[ 14 ]. All these patients had multiple cranial nerve palsies including facial and bulbar palsies.…”
Section: Discussionmentioning
confidence: 99%
“…Guillain-Barre syndrome (GBS) is a peripheral neuropathy caused by Schwann cell damage, possibly through an autoimmune mechanism. Although the incidence is relatively low, a portion of GBS patients show abnormal ABRs (Ropper and Chiappa, 1986;Nelson et al, 1988;Schiff et al, 1985;Ueda and Kuroiwa, 2008;Takazawa et al, 2012). Intriguingly, although hearing thresholds gradually recover in some patients, their ABR waveforms show persistent increases in interpeak latencies (Takazawa et al, 2012), suggestive of permanent myelin deficits in these patients.…”
Section: Peripheral Neuropathymentioning
confidence: 99%
“…Although the incidence is relatively low, a portion of GBS patients show abnormal ABRs (Ropper and Chiappa, 1986;Nelson et al, 1988;Schiff et al, 1985;Ueda and Kuroiwa, 2008;Takazawa et al, 2012). Intriguingly, although hearing thresholds gradually recover in some patients, their ABR waveforms show persistent increases in interpeak latencies (Takazawa et al, 2012), suggestive of permanent myelin deficits in these patients. Our recent study using mouse models showed that when Schwann cells are lost, they regenerate and remyelinate SGNs, but heminodes remain disrupted and ABR latencies prolonged (Wan and Corfas, 2017).…”
Section: Peripheral Neuropathymentioning
confidence: 99%